(untitled) (Research, Society and Development, 2022)
Aiming at the delimitation of the buoyancy of the maximum temperature (TX), minimum temperature (Tn) and average temperature (Tm) of the air in the municipal area of ​​Parnaguá and the lagoon of that municipality. With the development and agricultural expansion, large areas are being deforested, not taking into account the contribution of meteorological factors among them, especially temperatures, can minimize the occurrence of damage from anomalous effects that may happen. TX, Tn and Tm data estimated by the estima software were used - T between the years 1960 - 2019, monthly, annual, maximum and minimum values ​​were obtained. Observing the variability of TX, Tn and Tm, the hottest quarter and its monthly and annual values ​​were delimited, as well as the observed absolute maximum and minimum values. The results show that in the hot period the possibilities of fires and fires increase and in green areas it is beneficial to the production of pastures and grain. Such delimitations of the hottest quarters and the information on the times of lowest maximum air temperature served as a warning to federal, state, municipal authorities and decision makers to carry out better planning. The average temperature is the representation of the variability and its oscillations of extreme temperatures, any variability in these elements the average temperatures adapt to their oscillations and result from the synoptic systems active in the rainy and dry season as well as from the impacts on the environment and its elevation in relation to sea level.